ANALISIS PERGESERAN HORISONTAL WADUK SERMO TAHUN 2012-2013 BERDASARKAN HASIL HITUNG PERATAAN PARAMETER BERBOBOT - , DESSY APRIYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sermo Reservoir has various beneficial function for society. Its main function is as a container of water delivered for water supply, irrigation, and flood prevention.The reservoir can hold up to 25,000 m3 of water with 157 ha of widespread inundation. Reservoir construction has top width of 8 m, bottom width of 250 m, 190 m long and 56m high. Considering the big benefit of the reservoir for surrounding society, maintenance and supervision of the reservoir, one of many ways is monitoring the geometric deformations that may occur are highly required. This research was conducted by performing geodetic observations, namely measuring distances and horizontal angles between control points on the existing control network on Sermo Reservoir. Observations were conducted at two epochs, the first in 2012 and second in 2013. Number of control points at the reservoir were nine points, with 22 distance data, 85 angle data and 14 coordinate measurement data at each epoch. Data processing was performed using weighted parameters method and horizontal movement analysis was performed using net congruency test. The results of data processing was movement from 2 mm to 17 mm. Horizontal movement analysis with 95% confidence level and 103 degrees of freedom was that movement of occur had not been significant. That results was that horizontal movements within 1 year had not been occur on every existing control points.